2004
DOI: 10.1023/b:brea.0000041593.69178.57
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Analog α-TEA and Celecoxib Alone and Together Reduce Human MDA-MB-435-FL-GFP Breast Cancer Burden and Metastasis in Nude Mice

Abstract: Alpha-TEA, a nonhydrolyzable ether analog of vitamin E (RRR-alpha-tocopherol), and celecoxib, a specific COX-2 inhibitor, were delivered separately or in combination to investigate their anticancer properties, using MDA-MB-435-FL-GFP human breast cancer xenografts in nude mice. Liposomal formulated alpha-TEA administered as an aerosol and celecoxib fed at 500 or 1250 mg/kg diet for 31 days separately or in combination significantly reduced tumor volume in comparison to control (p < 0.001 for all treatment grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
1
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 15 publications
1
41
1
2
Order By: Relevance
“…With the use of other pre-clinical models, others have shown that a COX-2 inhibitor celecoxib inhibits angiogenesis and induces apoptosis in breast cancer cells in a mouse model of spontaneous metastasis (Basu et al, 2004). In another model involving MDA-435-FL-GFP human breast cancer xenografts in nude mice, Zhang et al (2004) showed that celecoxib inhibits overall tumor burden and lung metastasis. COX-2 could have yet additional roles including a role in the pre-malignant phenotype (Crawford et al, 2004) and a role in suppressing tumor-specific host immune responses (Kundu et al, 2005;Basu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…With the use of other pre-clinical models, others have shown that a COX-2 inhibitor celecoxib inhibits angiogenesis and induces apoptosis in breast cancer cells in a mouse model of spontaneous metastasis (Basu et al, 2004). In another model involving MDA-435-FL-GFP human breast cancer xenografts in nude mice, Zhang et al (2004) showed that celecoxib inhibits overall tumor burden and lung metastasis. COX-2 could have yet additional roles including a role in the pre-malignant phenotype (Crawford et al, 2004) and a role in suppressing tumor-specific host immune responses (Kundu et al, 2005;Basu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike RRR-α-tocopherol, α-TEA is not an antioxidant and it exhibits potent antitumor activity both in vivo and in vitro [4][5][6][7][8][9][10]. α-TEA has been shown to exhibit both antitumor and antimetastatic activity in animal xenograft and syngeneic mouse models of breast cancer when administered by aerosol and if formulated properly when administered orally, suggesting a possible therapeutic potential [4][5][6][7]. α-TEA is noteworthy not only for its ability to reduce tumor burden and metastases in vivo but also for its lack of toxicity toward normal cells and tissues in these animal models [4][5][6][7]11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, tocopheryl succinate and even more tocopheryl maleate (12) or the non-hydrolysable ether analog of a-tocopherol, a-TEA (2,5,7,8-tetramethyl-2R-(4R, 8R-12-trimethyltridecyl) chroman-6-yloxyacetic acid) (13) have been shown to have cell properties far stronger than a-tocopherol. As working hypothesis it can be suggested that the nonhydrolysable tocopheryl succinate and tocopheryl maleate may mimic and substitute for TP causing a permanent activation of cellular signals.…”
mentioning
confidence: 99%